From mind to mouth: event related potentials of sentence production in classic galactosemia. - Inge Timmers; Bernadette M Jansma; M Estela Rubio-Gozalbo (PLoS ONE)
Patients with classic galactosemia, an inborn error of metabolism, have speech and language production impairments. Past research primarily focused on speech (motor) problems, but these cannot solely explain the language impairments. Which specific deficits contribute to the impairments in language production is not yet known. Deficits in semantic and syntactic planning are plausible and require further investigation. In the present study, we examined syntactic encoding while patients and matched controls overtly described scenes of moving objects using either separate words (minimal syntactic planning) or sentences (sentence-level syntactic planning). The design of the paradigm also allowed tapping into local noun phrase- and more global sentence-level syntactic planning. Simultaneously, we recorded event-related potentials (ERPs). The patients needed more time to prepare and finish the utterances and made more errors. The patient ERPs had a very similar morphology to that of healthy controls, indicating overall comparable neural processing. Most importantly, the ERPs diverged from those of controls in several functionally informative time windows, ranging from very early (90-150 ms post scene onset) to relatively late (1820-2020 ms post scene onset). These time windows can be associated with different linguistic encoding stages. The ERP results form the first neuroscientific evidence for language production impairments in patients with galactosemia in lexical and syntactic planning stages, i.e., prior to the linguistic output phase. These findings hence shed new light on the language impairments in this disease.